2020
DOI: 10.3390/jmse8060436
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Mooring Line Test Procedures through the Application of a Round Robin Test Approach

Abstract: Innovation in materials and test protocols, as well as physical and numerical investigations, is required to address the technical challenges arising due to the novel application of components from conventional industries to the marine renewable energy (MRE) industry. Synthetic fibre ropes, widely used for offshore station-keeping, have potential application in the MRE industry to reduce peak mooring line loads. This paper presents the results of a physical characterisation study of a novel hybrid polyester-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…In units typical of textile materials, Figure S16 refers to a specific strength of 0.65 N tex –1 for DA-CMC/CNT@100, exceeding the mechanical performance of nanocellulose fibers (∼0.29 N tex –1 ) and polyester-polyolefin fiber yarns (0.59 N tex –1 ). 31 , 52 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In units typical of textile materials, Figure S16 refers to a specific strength of 0.65 N tex –1 for DA-CMC/CNT@100, exceeding the mechanical performance of nanocellulose fibers (∼0.29 N tex –1 ) and polyester-polyolefin fiber yarns (0.59 N tex –1 ). 31 , 52 …”
Section: Resultsmentioning
confidence: 99%
“…This strength improvement can be ascribed to the formation of more isotropic structures affecting the axial properties and enhancing the strength between neighboring building blocks as a consequence of an ordered packing. In units typical of textile materials, Figure S16 refers to a specific strength of 0.65 N tex –1 for DA-CMC/CNT@100, exceeding the mechanical performance of nanocellulose fibers (∼0.29 N tex –1 ) and polyester-polyolefin fiber yarns (0.59 N tex –1 ). , …”
Section: Resultsmentioning
confidence: 99%
“…The RR programme on mooring testing [73] found that ISO guidance on moorings [74] is suitable for ORE testing, with a recommendation that higher-frequency loading be incorporated.…”
Section: Testing Procedures and Preliminary Findingsmentioning
confidence: 99%
“…Synthetic mooring lines usually have relatively large elongations, even when made of novel types of rope [25,43]. Since Poisson's ratio for synthetic ropes can be assumed as 0.5 [44], a significant reduction of the outer rope diameter can be expected.…”
Section: Introductionmentioning
confidence: 99%